Correlating Sentence Repetition and Story Retelling For the Language Assessment of Greek-Cypriot Children - Agrotou, Ioulia (Department of Rehabilitation Sciences, Faculty of Health Sciences, Cyprus University of Technology, 2021)
This study investigates two tests, Sentence Repetition and the Bus Story Test, for linguistic evaluation of children and explores an association between them. Data was gathered from 78 Greek Cypriot children ages 5 through 10 from public schools in the cities of Limassol, Nicosia, and Pafos. Information collected before the testing shows that all the families had a similar socioeconomic status. The Sentence Repetition was designed with complex syntactic structures that can be produced by typically developing children that speak Standard Modern Greek (SMG) and Cypriot Greek (CG). The Bus Story test used in this study was a Greek adaptation of the Renfrew Bus Story Test-North American Edition. The measures of the Bus Story test included seven variables related to recall, syntax and vocabulary which were compared with the two measures of the Sentence Repetition test. The hypothesis was that there was a positive correlation between the scores of both tests in the performance of each child. Statistical analysis showed a correlation between specific variables of the Bus Story Test and Sentence Repetition only in the younger age group (5;00-7;09) and not in the older group (7;09-10;08). The initial aim of this research was to establish an association between the results of the two tests in order to rationalize the methods of assessment in Typical Language Development (TLD) and Developmental Language Disorder (DLD). The limited evidence provided by this study for a direct relation between the two tests does not allow for the dispensing of any of the two tests, until more research is conducted in the future.
Keywords: Greek Cypriot; Narrative retelling; Sentence Repetition; Typical Language Development (TLD); Bus Story Test; Ελληνοκύπριος; Aφηγηματική επαναφορά; Eπανάληψη προτάσεων; Aνάπτυξη τυπικής γλώσσας